Global and regional value chains in Latin America in times of pandemic - Vanessa Alviarez (Inter-American Development Bank (IDB), 2022)
Global value chains (GVCs) provide countries with opportunities to diversify trade, and boost productivity and growth by specializing in one stage of the production process. However, for the most part, Latin America and the Caribbean participation in GVCs remains low (18 percent) compared to Asia (28 percent) and Europe (34 percent). The COVID-19 pandemic, plus concerns regarding protectionism and the more frequent occurrence of natural disasters, have provided incentives for countries and companies to reassess their positions in global value chains. This crisis has taken a huge toll on trade, but it could also be an opportunity to boost regional integration and value chains within the region. Despite the crisis, some firms have performed well, even in those sectors where global demand has fallen, while others have lost market share. This paper analyzes the performance of individual firms, drawing on the study of rich micro data, to understand their different capacity of trade creation and destruction over the crisis. Results suggest five firm characteristics play a key role in explaining export performance during the pandemic: i) firm size, ii) diversification of export markets, iii) importer status of the firm, iv) distance from foreign suppliers, and v) performance of the firm's suppliers and customers. The results are then used to outline policies fostering firms' participation in global value chains.
Keywords: F23; F14; L14; L23; 330; Global value chains; COVID-19; Production networks; Shockpropagation